State of the Climate in 2021 - Blunden, Jessica; Boyer, Tim; Grooss, Jens-Uwe; Müller, Rolf; Bernhard; Fioletov; Ialongo; Johnsen; Lakkala; Manney, G. (Bulletin of the American Meteorological Society, 2022)
Past emissions of man-made chlorine-containing substances, such as chlorofluorocarbonsCFCs), have caused substantial chemical depletion of stratospheric ozone (WMO 2018). The resulting ozone loss led to increases of ultraviolet (UV) radiation at Earth’s surface with adverse effectsn human health and the environment (Barnes et al. 2019; EEAP 2019). The chemical destruction of polar ozone occurs within a cold stratospheric cyclone known as the polar vortex, whichorms over the North Pole every winter (WMO 2018). The polar vortex between November 2020nd April 2021 was weakened by a Sudden Stratospheric Warming (SSW; see Sidebar 5.2) event inarly January 2021 that decreased depletion of stratospheric ozone in the Northern Hemisphereuntil at least April. A similar SSW event occurred in January 2013. The progressions of chemicalzone loss in the winters of 2012/13 and 2020/21 are therefore compared below.